The Effect Of Open Unemployment On Criminality In Banjarmasin City 2018-2022: Using Eviews 12 Perspectives Of Shariah Economics - Aisyah, Lisda; Nilasari, Erissa (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2024)
This research is motivated by the problem of poverty in Banjarmasin City which is caused by the imbalance between labor force growth and job creation. Increased destruction will have an impact on crime. This research aims to: 1) describe the efforts made to reduce crime in Banjarmasin. 2) illustrates that the increasing number of poverty and low income are one of the factors causing the increase in criminal cases in Banjarmasin. 3) describe the impact of poverty on crime in Banjarmasin. This type of research is quantitative descriptive research. The data used in this research is secondary data in the form of time series data obtained from the Central Statistics Agency. The analysis technique used is simple linear regression using the Eviews 12 program. The results of this research prove that poverty has a big impact on crime that occurs in the City of Banjarmasin, that is because the impact of crime only simultaneously has a significant influence on crime in the City of Banjarmasin, This can be seen from the results of the F Test where the Prob (F-Statistic) value = 0.103287 < 0.05 and F_statistics = 5.372431. The findings of this study indicate that unemployment does not have a direct effect on crime in Banjarmasin and is influenced by other factors. In Shariah Economics, it is important to implement economic justice and social assistance to prevent crime even though unemployment is high.